School-Based Intervention to Enhance Parent-Adolescent Sexual Communication: A Literature Review - Rachmawati, Annisa; Widyatuti; Sari, Indah Permata; Permatasari, Henny (Babali Nursing Research, 2025)
Introduction: Sexual communication between parents and adolescents positively impacts the prevention of premarital sexual behaviour. School-based intervention is a promising approach. This review aims to identify school-based interventions that enhance parent-adolescent sexual communication and assess the quality of the studies. Methods: This literature review followed the PRISMA protocol. Four databases—PubMed, ProQuest, Scopus, and Taylor & Francis—were searched using the keywords “adolescent,” “school-based intervention,” and “parent-adolescent communication.” Inclusion criteria were school-based interventions targeting students and evaluating parent-adolescent sexual communication. Studies involving certain medical conditions and LGBTQ groups were excluded. Results: Eight studies were included from 3854 articles. Interventions targeted students from sixth to 11th grade and involved parents. Various methods were used, including lectures, group discussions, role plays, demonstrations, and art-based activities. Some programs were integrated into school subjects, while others utilized technology. Parental involvement was facilitated through assignments that required collaboration between students and their parents. Additionally, several studies organized dedicated sessions or parenting classes for parents. Conclusion: School-based interventions that involve parents and use diverse delivery methods can effectively improve parent-adolescent sexual communication. However, most studies were conducted in the United States, several were over ten years old, and some had limited methodological quality, which may affect the applicability of findings. Schools are recommended to integrate reproductive health content, especially that which fosters parent-adolescent sexual communication, into existing curricula. Additionally, combining student and parent education through joint assignments or organizing parenting classes may enhance the impact of such interventions.